1976 IMO Problems/Problem 6

Revision as of 16:30, 29 January 2021 by Hamstpan38825 (talk | contribs)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)


A sequence $(u_{n})$ is defined by

\[u_{0} = 2 \quad u_{1} = \frac {5}{2}, u_{n + 1} = u_{n}(u_{n - 1}^{2} - 2) - u_{1} \ \text{ for } n = 1,\cdots\]

Prove that for any positive integer $n$ we have

\[\lfloor u_{n} \rfloor = 2^{\frac {(2^{n} - ( - 1)^{n})}{3}}\]

(where $\lfloor x\rfloor$ denotes the smallest integer $\leq$ $x$)$.$


Let the sequence $(x_n)_{n \geq 0}$ be defined as \[ x_{0}=0,x_{1}=1, x_{n}=x_{n-1}+2x_{n-2} \] We notice \[x_n=\frac{2^n-(-1)^n}{3}\] Because the roots of the characteristic polynomial $x_{n}=x_{n-1}+2x_{n-2}$ are $-1$ and $2$. \\newline We also see $\frac{2^1-(-1)^1}{3}=1=x_1$, $\frac{2^2-(-1)^2}{3}=1=x_2$ We want to prove \[2^{x_{n}-2x_{n-1}}+2^{-x_{n}+2x_{n-1}}=2^{x_1}+2^{-x_1}\] This is done by induction

Base Case: For $n=1$ ses det $2^{1-0}+2^{0-1}=2^{1}+2^{-1}$

Inductive step: Assume $2^{x_{n-1}-2x_{n-2}}+2^{-x_{n-1}+2x_{n-2}}=2^{x_1}+2^{-x_1}$ We notice \begin{align*}  2^{x_{n}-2x_{n-1}}+2^{-x_{n}+2x_{n-1}} &=2^{x_{n-1}+2x_{n-2}-2x_{n-1}}+2^{-(x_{n-1}+2x_{n-2})+2x_{n-1}}\\ &=2^{-x_{n-1}+2x_{n-2}}+2^{x_{n-1}-2x_{n-2}}\\ &=2^{x_1}+2^{-x_1} \end{align*} We then want to show \[a_n=2^{x_n}+2^{-x_n}\] This can be done using induction

Base Case

For $n=1$, it is clear that \[a_1=\frac{5}{2}\] and \[2^{x_1}+2^{-x_1}=2^1+2^{-1}=2+\frac{1}{2}=\frac{5}{2}\] Therefore, the base case is proved.

Inductive Step

Assume for all natural $k<n$ at $a_k=2^{x_k}+2^{-x_k}$\newline Then we have that: \begin{align*}  a_n &=  a_{n}(a_{n-1}^{2}-2)-a_{1} \\   &=  (2^{x_{n-1}}+2^{-x_{n-1}})((2^{x_{n-2}}+2^{-x_{n-2}})^2-2)-(2^{x_{1}}+2^{-x_{0}}) \\  &= (2^{x_{n-1}}+2^{-x_{n-1}})((2^{x_{n-2}})^2+(2^{-x_{n-2}})^2+2*2^{x_{n-2}}*2^{-x_{n-2}}-2)-(2^{x_{1}}+2^{-x_{0}}) \\  &=(2^{x_{n-1}}+2^{-x_{n-1}})((2^{2x_{n-2}})+(2^{-2x_{n-2}})+2*2^{x_{n-2}-x_{n-2}}-2)-(2^{x_{1}}+2^{-x_{0}}) \\  &=(2^{x_{n-1}}+2^{-x_{n-1}})((2^{2x_{n-2}})+(2^{-2x_{n-2}})+2-2)-(2^{x_{1}}+2^{-x_{0}}) \\ &=2^{x_{n-1}}*2^{2x_{n-2}}+2^{-x_{n-1}}2^{-2x_{n-2}}+2^{x_{n-1}}*2^{-2x_{n-2}}+2^{-x_{n-1}}*2^{2x_{n-2}}-2^{x_{1}}-2^{-x_{0}}\\ &=2^{x_{n-1}+2x_{n-2}}+2^{-(x_{n-1}+2x_{n-2}})+2^{x_{n-1}-2x_{n-2}}+2^{-x_{n-1}+2x_{n-2}}-2^{x_{1}}-2^{-x_{0}}\\ &=2^{x_{n}}+2^{-x_{n}}+2^{x_{n-1}-2x_{n-2}}+2^{-x_{n-1}+2x_{n-2}}-2^{x_{1}}-2^{-x_{0}} \end{align*} From our first induction proof we have that: \[2^{x_{n-1}-2x_{n-2}}+2^{-x_{n-1}+2x_{n-2}}=2^{x_1}+2^{-x_1}\] Then: \[a_n=2^{x_n}+2^{-x_n}+2^{x_1}+2^{-x_1}-(2^{x_1}+2^{-x_1})=2^{x_n}+2^{-x_n}\] We notice $\left[a_n\right]=\left[2^{x_n}+2^{-x_n}\right]=2^{x_n}$, Because $2^{x_n} \in \mathbb{N}$ and $2^{-x_n}<1$, for all $n>0$ Finally we conclude \[\left[a_n\right]=2^{\frac{2^n-(-1)^n}{3}}\]

See also

1976 IMO (Problems) • Resources
Preceded by
Problem 5
1 2 3 4 5 6 Followed by
Final Question
All IMO Problems and Solutions
Invalid username
Login to AoPS